Stein’s Anthropological Approach to the Humanities - Janik, Piotr (Studia Philosophiae Christianae, 2023)
Should we approach the lived experience and/or understand the other with the sense of things? If this is the case, how are we to treat the human experience par excellence? Paradoxically, Edith Stein gives a fresh meaning to the Husserlian term “leibliche Selbstgegebenheit.” In contrast to Max Scheler’s account, she develops the “persönliche Note” criterion of authenticity. And against Maetin Heidegger’s existential philosophy, a concern for human existence itself resonates. Based on these three dimensions, this article discusses the idea of “the lived experience” according to Edith Stein, that is, the human experience contemplated by the humanities. -------------------------- Received: 03/02/2023. Reviewed: 16/03/2023. Accepted: 30/03/2023.